Temperature shocks and human mortality in the Philippines - Intalan, Louie Aldrin M.; Takahashi, Shingo (2017)
Access online through this link: https://journals.upd.edu.ph/index.php/SURP/article/view/8933/7880
Keywords: Climate change; Climate change and health; Temperature; Mortality